Analysis of Students’ Preferences as Academic Source of Information (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
The research topic focused on the analysis of the library and Internet as an academic source of information. The researchers chose this topic because the library and/or Internet are the most commonly used sources by the students of Bestlink College of the Philippines to get information. The purpose of this research is to let the students know what is best to use to improve their academic performance. It will also allow them to be aware of how to get information from the Internet and library. The researchers used the survey method because this is the most applicable method to use in gathering necessary data. It is also defined as a research method for collecting data from a predefined group of respondents to gain information. The researchers used convenience sampling because the respondents were chosen based on their availability. Based on the results of the study, the Internet and library helped the students to find information and improve their academic performance. In terms of the process on how to find information, the library is being left behind because the Internet is considered the most powerful and fastest tool that can be used by students to get information nowadays. Using the two can improve the students’ academic performances because it will be easy for them to gather information. The researchers recommended that students should use the library and the Internet to gather information because it will help them to expand their knowledge and develop their thoughts about getting preferences. More focus must be given to encourage the students to continuously use the library to obtain more reliable information because books have been reviewed before publishing. The use of the Internet was also recommended by the researchers because it also provides timely information and is constantly being updated. A rule that may allow the students to spend one to two hours using the library must be implemented.
Keywords: analysis, students’ preferences, academic sources, library, internet